Gestión de Procesos soportados por Sistemas de Información en la Dirección de Posgrado de la Universidad Técnica de Cotopaxi. - Andrade Villacís, Xavier Mauricio (2020)
The research developed starts from the following problem: How to improve the efficiency in the development of administrative and academic management activities in the Postgraduate Direction at the Technical University of Cotopaxi? ... In order to solve the problem, it is determined as a general objective: To propose a general procedure to improve the efficiency of the Postgraduate activities of the Technical University of Cotopaxi. For the development of the inquiry, a mixed investigation approach is used in which it operates with the following methods: deductive inductive, synthetic analytical, functional structural systemic, documentary analysis, user criteria, mode and mean to process and interpret the data derived from user criteria. In addition, the following procedures will be used: Administrative tools such as SIPOC to define: Suppliers / Inputs / Outputs / Processes / Clients, and to determine how the information flows. All of which allowed the general procedure, the general diagram of administrative and academic management activities in the Graduate School and the diagrams of each specific procedure to be obtained as essential results.